The Significance of the Probabilistic Voting Theorem - Dan Usher (Queen's University, Department of Economics, 1990)
Public decision-making by majority rule is open to the danger of exploitation of minorities by majorities. Since any majority can employ the vote to expropriate the corresponding minority, it would seem that there can be no electoral equilibrium allocation of income or transfers in a democratic society and that democracy itself might be unstable. Much of democratic theory is devoted to the study of how this danger can be averted. The probabilistic voting theorem establishes that a degree of voter insensitivity to offers of rival political parties imparts an electoral equilibrium where it would not otherwise exits. The theorem is valid on its assumptions, but those assumptions are considerably stronger, and the theorem is less comforting about the prospects for the stability of democratic government, than one might at first suppose.
Keywords: 330